Structural failure study of truck rear wheel drive axle with defect variation using finite element method - Husaini, Husaini; Rizki, Ulil; Ali, Nurdin (Politeknik Negeri Lhokseumawe, 2024)
A truck is a major form of transporting goods on land because of its efficiency in terms of cost and effectiveness. Increased truck usage has heightened the risk of component failure, particularly in the rear-wheel-drive axle, which is prone to structural problems. Therefore, this study aimed to analyze the causes of rear-wheeldrive axle failure in trucks through numerical simulations based on the finite element method, using Finite Element Modeling and Postprocessing (FEMAP) software. The axle material used was AISI 4140, with four test models, including a version without defects and three other models with variations in defects at certain locations. During the investigation, the analysis was conducted to observe the effect of stress on axle performance under various defect conditions. The simulation results showed the maximum von Misses stress on the shaft without defects reached 115.19 MPa, which was significantly lower than the yield strength limit of 415 MPa of the material. The maximum shear stress of 124.67 MPa also remained lesser compared to the material allowable limit of 239.45 MPa, showing that the shaft was safe in a condition without defects. However, in the shaft model with defects, stress intensity factor (KI) values were recorded at 17.80, 15.01, and 20.325 MPa.m1/2, which exceeded the material fracture toughness (KIC) value of 10 MPa.m1/2. The results signified that KI KIC condition, facilitating accelerated crack propagation on the shaft, showing the potential for structural failure. This study provided a deep understanding of the importance of defect mitigation to maintain the reliability and safety of truck operations